Analysis of the existing mechanism of macroeconomic regulation of public procurement - Matsapura Е. V. (Ways to Improve Construction Efficiency, 2019)
According to the results of the content analysis of digital transformations, the general and distinctive features of the implementation of strategic documents that ensure the formation of the digital economy in different countries are highlighted. The identified patterns have made it possible to argue that the overall digital economy development strategy in Ukraine is in line with global trends. The imperatives of digitization of construction enterprises through the prism of vectors and forms of realization of investment-innovative activity are offered, because in the current economic conditions one of the important factors of effective functioning of the production and economic system in the long term is digital transformation and effective mechanism of attracting investments for its realization. According to the results of the content analysis of digital transformations, the general and distinctive features of the implementation of strategic documents that ensure the formation of the digital economy in different countries are highlighted. The identified patterns have made it possible to argue that the overall digital economy development strategy in Ukraine is in line with global trends. The imperatives of digitization of construction enterprises through the prism of vectors and forms of realization of investment-innovative activity are offered, because in the current economic conditions one of the important factors of effective functioning of the production and economic system in the long term is digital transformation and effective mechanism of attracting investments for its realization. According to the results of the content analysis of digital transformations, the general and distinctive features of the implementation of strategic documents that ensure the formation of the digital economy in different countries are highlighted. The identified patterns have made it possible to argue that the overall digital economy development strategy in Ukraine is in line with global trends. The identified patterns have made it possible to argue that overall the digital economy development strategy in Ukraine is in line with global trends